A new species of Potentilla sect. Leptostylae from central Burma - Ikeda, H.; Ohba, H. (Edinburgh Journal of Botany, 2010)
A new species of Potentilla sect. Leptostylae (Rosaceae), P. montisvictoriae, endemic to Mt Victoria, C Burma, is described. Potentilla montisvictoriae differs from P. leuconota D. Don in having free auricles on the stipules of the radical leaves, patent or descending hairs on the rachis and peduncles, obovate petals, styles longer than ovaries and entire or shallowly incised auricles on the stipules of the cauline leaves.